Economics assessment and impact of climate change on rice production in selected granary area in Malaysia - Engku Ariff, Engku Elini (2016)
Two of the major challenges to agriculture are the effective management of inputs involved in production and the impact of climate change on production. In Malaysia, as in other countries, input costs across rice farms within a particular year are highly variable, suggesting that there is scope for improving the efficiency of production. Climate change, particularly in the form of changed temperatures and rainfall, is likely to affect rice yields. In this thesis, we focus first on technical efficiency associated with rice producing farms in three granary areas in Malaysia. Technical efficiency (TE) was measured using non-parametric (DEA) and parametric approaches (SFA). For DEA, TE was analysed for the input-oriented approach in which inputs are minimised for a given level of rice production while for SFA, Translog production functions were used to represent the efficiency frontier of the industry. Primary data for a season of rice production were collected in 2010/ 2011; sample size was 100 farmers for each of three granaries: MADA, situated in the north of Peninsular Malaysia, KADA in the west and PBLS in North West Selangor. Results showed that, under the constant returns to scale (CRS) assumptions, KADA showed the lowest average efficiency at 65.2%. The other two granaries can also maintain output while reducing inputs: by approximately 27% in both cases. All efficiencies were greater under the variable returns to scale (VRS) assumption, with the differences between CRS and VRS values for KADA suggesting a considerable amount of scale inefficiency within this region. Results using the SFA approach were slightly higher as compared to TE from DEA. All methods used suggested that efficiency of rice production in Malaysia could be improved. Tobit regression was applied to indicate the relationship between TE and farm characteristics and management factors. Factors such as race, ownership, soils and variety were identified to have significant effects on the level of efficiency. With respect to climate change, to assess future rice yields, the DSSAT model was used to predict yields for the 2050s and 2080s by using generated weather data under alternative climate change scenarios.. The results showed that climate change has a largely detrimental impact on rice yield in the future; the longer climate change exists, the worse the impact. For every 1% increase in temperature, yield was estimated to fall in a range of 7% to 21%. As yield was predicted to be less due to climate change, other things being equal, efficiency would fall as well. In Malaysia the rice industry has been sustained, in part, by government intervention, especially input subsidy. In the future, adaptation to climate change should have a higher priority, as should policies that help the industry to sustain itself through improved competitiveness rather than from government subsidy.